ANALYTIC HIERARCHY PROCESS METODE PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT PADA KOPERASI MANDIRI UTAMA - kenali, fitria (IIB Darmajaya, 2013)
In disbursing loans to the members, the Cooperative Mandiri Utama should consider several things including, the files submission must be complete, been already had Â a family, living in the same area with ââthe Cooperative office, already had job security and / effort that is being/has been running. Method of analytic hierarchy process or AHP is often called one of the methods that is used for decision making in a variety of issues such as decision-making (of) major selections, the winer of bidder project, the selection of housing, etc. Method of analytic hierarchy process is easily understood and applied to various types of cases that can be generally described the characteristics that the final result was obtained by calculating the percentage who belong to certain elements of the calculation. The new application system in a data processing Lending Decision Support System on Cooperative Mandiri Utama AHP method has to be used to process credit analysis and decision concludes the creditworthiness so it facilitate the cooperative Mandiri Utama in making decisions on loans made ââby the cooperative. Keywords : Lending , cooperative , AHP